ANALISIS KEMAMPUAN KOMUNIKASI TERTULIS SISWA PADA PEMBELAJARAN GEOGRAFI - Addawiyah, Jamiatul; Bigharta Bekti Susetyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Written communication is a fundamental competency in geography education for articulating spatial analysis and scientific arguments. However, the assessment of this aspect is often hinSdered by the lack of standardized instruments. This study aims to analyze the quality of assessment instruments for students’ written communication skills and to measure students’ achievement in terms of validity, reliability, gender, and Higher Order Thinking Skills (HOTS) dimensions. The research method used a descriptive quantitative approach with a sample of 25 students who were tested using 10 case-study-based essay questions on disasters. Data were analyzed using Pearson Product Moment validity tests, Cronbach’s Alpha reliability, and comparative descriptive statistics. The results indicate that all items were deemed valid with calculated r values ranging from 0.764 to 1.000 (exceeding the critical r value of 0.3961), and the instrument demonstrated very high reliability with an Alpha value of 0.973. Overall, 92% of students fell into the “Very Good” proficiency category with an average score of 92.24. Gender analysis revealed that female students demonstrated higher performance consistency (100% in the “Very Good” category) compared to male students, who exhibited greater score variability. Additionally, the instrument, which integrates 46% of items at the C4 (Analysis) cognitive level, proved capable of accurately measuring students’ HOTS abilities. It is concluded that this assessment instrument is suitable for use in geography assessment, and strong written communication skills serve as a crucial foundation for students’ success in solving HOTS-based questions.